The genetics of primary dystonias and related disorders. - Németh, A (2002)
Dystonias are a heterogeneous group of disorders which are known to have a strong inherited basis. This review details recent advances in our understanding of the genetic basis of dystonias, including the primary dystonias, the 'dystonia-plus' syndromes and heredodegenerative disorders. The review focuses particularly on clinical and genetic features and molecular mechanisms. Conditions discussed in detail include idiopathic torsion dystonia (DYT1), focal dystonias (DYT7) and mixed dystonias (DYT6 and DYT13), dopa-responsive dystonia, myoclonus dystonia, rapid-onset dystonia parkinsonism, Fahr disease, Aicardi-Goutieres syndrome, Hallervorden-Spatz syndrome, X-linked dystonia parkinsonism, deafness-dystonia syndrome, mitochondrial dystonias, neuroacanthocytosis and the paroxysmal dystonias/dyskinesias.